(untitled) (Philological Studies, 2019)
The toponymic doublets or two-named toponyms characteristize the Slavic toponymy and, therefore, the Macedonian. They are results of a process that started in the past, exists in the present and will continue in the future. In the collected material, there are 65 registered toponymical doublets that, according to their structure, are classified in nine groups that mainly reflect the following few particularities: 1. old versus new names, 2. dialect characteristics that tends to change, 3. long toponymic form that tends to transform in more economic, short form. The data analysis includes a definition of the appellatives and their origin for each doublet unit.